Filogeografia de Drosophila maculifrons e Drosophila griseolineata (Diptera, Drosophilidae) na região Sul do Brasil - De Re, Francine Cenzi (2012)
The Quaternary period was marked by considerable changes on climate and vegetation. In the Southern Hemisphere, glaciations were milder than in the Northern Hemisphere, however, there were temperature reductions, and the climate became drier. Thus, climate-related modifications occurred in the Atlantic forest vegetation, which contracted its distribution being substituted towards other types, such as Cerrado and Caatinga . The original Atlantic forest vegetation became restricted to moist locations with milder temperatures, called refuges, which sheltered most part of the biodiversity at this time. It is known that such paleoclimatic changes affected the population dynamics of many species, especially in the Northern Hemisphere. However, it is still not clear how much these impacts influenced the species of the Neotropical region. The two species of this study, Drosophila maculifrons and Drosophila griseolineata, belong to the guaramunu group of Drosophila, and are considered sister-species that diverged about four million years ago. However, disregarding their close phylogenetic relationships, they present some distinct ecological patterns, the first species being more generalist, and the second more restricted to forest environments. Due to this ecological heterogeneity, these two species are potential indicators of the genetic consequences caused by the climatic fluctuations of the Quaternary, especially in face of a comparative perspective. The aims of this study were to evaluate the intraspecific diversity of different D. maculifrons and D. griseolineata populations, analyze the structure of individuals and populations in these two species of the guaramunu group and identify the ecological and evolutionary forces that modeled their distribution in Southern/Southeastern Brazil. In order to do so, 114 individuals were collected along the South, Southeast and Center-west regions of Brazil and Medellin, Colombia. Modeling analysis was performed, together with phylogenetic and phylogeographic analyses, with the last based in sequences of COI (Cytochrome Oxidase Subunit I) and COII (Cytochrome Oxidase Subunit II) genes. In general, the results that inferred the distribution of the most suitable habitat for each species indicate that the two species occur in sympatry at several points, although D. maculifrons is more widely distributed than D. griseolineata, at least in the brazilian territory. According to our phylogeographic analysis, D. maculifrons presents low levels of diversity and structure for mtDNA, which could be explained by a recent populational expansion event, dated for about 20 to 30 thousand years ago. On the other hand, D. griseolineata shows moderate levels of diversity and population structure, and its populations seem to have remained stables along time, showing a pattern of isolation by distance. So, it is interesting to evaluate the ecological and/or evolutionary factors which are responsible for all this difference, and this work represents a first step towards this understanding.